An example of clinical inertia in geriatrics - Tahir Belice; Mustafa Ubay; Fatma O Gozubuyuk; Rasim S Yilmaz; Arif Yuksel (Journal of Family Medicine and Primary Care, 2020)
Background: As we know that close contact is the main reason of the contagious diseases, caregivers are at higher risk for diseases that we can prevent by vaccines. In present study, we aim at revealing an example of clinical inertia in geriatrics, which shows us the status of vaccination both in a group of older patients and their caregivers. Materials and Methods: Both the caregivers and their dependent geriatric patients were included, and the selection of the participants was designed on a random and volunteer basis. We performed the study with a phenomenological design and asked the participants their vaccination status. For the participants that were not vaccinated, the reasons were questioned with a demographic form. Correlations between parameters were analyzed with an independent t-test and analysis of variance. SPSS (IBM SPSS for Windows, ver.24) was used to analyze the data, which were saved in excel files. Results: A total of 144 caregivers with 21 men (14.6%) and 123 female (85.4%) were included in the study. A total of 111(77.1%) caregivers had never been vaccinated before, while 21 (14.6%) caregivers were vaccinated occasionally, and finally, 12 (8.3%) caregivers were vaccinated on a regular base. The vaccination status of the older adults was as follows: 42 patients (29.2%) had never been vaccinated before, 60 (41.7%) had been vaccinated occasionally, and 42 (29.2%) patients had been vaccinated regularly. Conclusion: The vaccination rates of caregivers and older patients were lower than we expected, so primary-care providers need to plan more vaccination awareness studies in social media and communities. Clinical inertia might be an essential reason in the lower vaccination rates of the caregivers and older adults' population.